2008
DOI: 10.1111/j.1574-6968.2008.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression and extracellular secretion of the collagenolytic enzymes by the pathogen Vibrio parahaemolyticus

Abstract: Vibrio parahaemolyticus, a causative agent of wound infections as well as food poisoning, harbors two collagenase genes: vppC and prtV. When cultivated at 26 degrees C in gelatin broth supplemented with 3.0% NaCl, significant collagenolytic activity was detected in the culture supernatant at the early stationary phase. Native polyacrylamide gel electrophoresis analysis revealed a 90-kDa protein, and N-terminal amino acid sequencing showed that this protein was VppC, generated through truncation of 72 N-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…5A to D). Supporting these findings, the N-terminal amino acid sequencing analysis showed that the corresponding two forms of proteases observed in the supernatants isolated from early-stationary-phase cultures of V. parahaemolyticus were constituents of the VppC collagenase (63). Further, the processing of VchC was stimulated by a yet-to-be identified extracellular factor(s) (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…5A to D). Supporting these findings, the N-terminal amino acid sequencing analysis showed that the corresponding two forms of proteases observed in the supernatants isolated from early-stationary-phase cultures of V. parahaemolyticus were constituents of the VppC collagenase (63). Further, the processing of VchC was stimulated by a yet-to-be identified extracellular factor(s) (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…V. parahaemolyticus is a leading cause of bacterial gastroenteritis in Asia as well as in other countries Wong et al 2000;McLaughlin et al 2005;Shigeaki et al 2012), and is attracting increasing interest worldwide where raw or undercooked seafood is often consumed (Chao et al 2009). It causes wound infections in those exposed to contaminated water (Miyoshi et al 2008). It also causes septicemia, particularly in immunocompromised people .…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of these enzymes is mainly correlated with the phylogenetic relationship of the three bacteria as follows: Clostridium, such as Clostridium histolyticum [7] and Clostridium perfringens [8]; Vibrio, such as Vibrio alginolyticus [9] and Vibrio parahaemolyticus [10]; and Porphyromonas, such as Porphyromonas gingivalis [11] and Porphyromonas endodontalis [12]. These microbes are pathogens or conditional pathogenic bacteria which potentially produce toxin.…”
Section: Introductionmentioning
confidence: 99%